2008
DOI: 10.1002/clc.20262
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Heart Failure in a Tertiary Pediatric Center

Abstract: Background: In contrast to the adult age group, epidemiologic studies on heart failure (HF) in the pediatric population are lacking. The aim of this prospective study was to analyze the epidemiology of HF during infancy and childhood. Methods: Of the 1,196 children with congenital and acquired heart diseases, primarily diagnosed during a 10-y period in one hospital, we identified those patients who developed HF. Results: Within 10 y, 1,196 children with heart disease were indexed. Heart failure occurred in 124… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 11 publications
(6 reference statements)
2
54
0
3
Order By: Relevance
“…reported that only 10% of their patients in a tertiary care pediatric cardiology care setting developed symptomatic HF. [4]…”
Section: Epidemiologymentioning
confidence: 99%
“…reported that only 10% of their patients in a tertiary care pediatric cardiology care setting developed symptomatic HF. [4]…”
Section: Epidemiologymentioning
confidence: 99%
“…39 Two studies of heart failure in children, each covering 10 years, have been reported recently from European tertiary care facilities. 40,41 Children with heart failure represented 10% to 33% of all cardiac admissions. Slightly more than half of the pediatric heart failure cases reported in both studies were due to congenital heart disease, although the incidence of heart failure in children with congenital heart disease was only 6% to 24%.…”
Section: Classificationmentioning
confidence: 99%
“…Increasingly, genetic abnormalities are being identified in pediatric cardiomyopathy patients that result in systolic and/or diastolic dysfunction [22]. In complex congenital heart disease, ventricular morphology is often abnormal in addition to systolic dysfunction and arrhythmias and cyanosis can contribute to the development or severity of heart failure [16,23,24]. There is some evidence to support disruption of the neurohumoral axis in pediatric heart failure due to systolic ventricular dysfunction, however in patients with structural heart disease the data is conflicting [25][26][27][28].…”
Section: Study Rationalementioning
confidence: 99%